Seasonal variations in body composition, maximal oxygen uptake, and gas exchange threshold in cross-country skiers - Polat M; Korkmaz Eryılmaz S; Aydoğan S (Dove Medical Press, 2018)
Metin Polat,1 Selcen Korkmaz Eryılmaz,2 Sami Aydoğan3 1School of Physical Education and Sports, Erciyes University, Kayseri, Turkey; 2School of Physical Education and Sports, Cukurova University, Adana, Turkey; 3Department of Physiology, Faculty of Medicine, Erciyes University, Kayseri, Turkey Introduction: In order to ensure that athletes achieve their highest performance levels during competitive seasons, monitoring their long-term performance data is crucial for understanding the impact of ongoing training programs and evaluating training strategies. The present study was thus designed to investigate the variations in body composition, maximal oxygen uptake (VO2max), and gas exchange threshold values of cross-country skiers across training phases throughout a season. Materials and methods: In total, 15 athletes who participate in international cross-country ski competitions voluntarily took part in this study. The athletes underwent incremental treadmill running tests at 3 different time points over a period of 1 year. The first measurements were obtained in July, during the first preparation period; the second measurements were obtained in October, during the second preparation period; and the third measurements were obtained in February, during the competition period. Body weight, body mass index (BMI), body fat (%), as well as VO2max values and gas exchange threshold, measured using V-slope method during the incremental running tests, were assessed at all 3 time points. The collected data were analyzed using SPSS 20 package software. Significant differences between the measurements were assessed using Friedman’s twoway variance analysis with a post hoc option. Results: The athletes’ body weights and BMI measurements at the third point were significantly lower compared with the results of the second measurement (p<0.001). Moreover, the incremental running test time was significantly higher at the third measurement, compared with both the first (p<0.05) and the second (p<0.01) measurements. Similarly, the running speed during the test was significantly higher at the third measurement time point compared with the first measurement time point (p<0.05). Body fat (%), time to reach the gas exchange threshold, running speed at the gas exchange threshold, VO2max, amount of oxygen consumed at gas exchange threshold level (VO2GET), maximal heart rate (HRmax), and heart rate at gas exchange threshold level (HRGET) values did not significantly differ between the measurement time points (p>0.05). Conclusion: VO2max and gas exchange threshold values recorded during the third measurements, the timing of which coincided with the competitive season of the cross-country skiers, did not significantly change, but their incremental running test time and running speed significantly increased while their body weight and BMI significantly decreased. These results indicate that the cross-country skiers developed a tolerance for high-intensity exercise and reached their highest level of athletic performance during the competitive season. Keywords: athletic performance, aerobic capacity, winter sport